+0  
 
 #1
avatar
0

Is this a question?

 Dec 16, 2020
 #2
avatar+114221 
+1

(1)   log 7 x + log 7 y  - log 7 z

 

Note that  log x + log y  = log (xy)

And  log  x  - log y  = log (x / y)

 

So....we have

 

log 7 ( xy  / z ) 

 

 

cool cool cool

 Dec 16, 2020
 #3
avatar+114221 
+1

e (4/3)Ln 2 - 1  =  

 

e4/3 Ln 2 /  e   =

 

e Ln2(4/3)  / e           note that  e ln a  = a

 

24/3  / e  =

 

16 1/3   / e   =

 

2∛2 / e

 

cool cool cool

 Dec 16, 2020

31 Online Users

avatar
avatar
avatar
avatar